2021
DOI: 10.1002/1873-3468.14078
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transfer between endoplasmic reticulum and mitochondria in liver diseases

Abstract: Calcium (Ca 2+) is a second messenger essential for cellular homeostasis. Inside the cell, Ca 2+ is compartmentalized and exchanged among organelles in response to both external and internal stimuli. Mitochondria-associated membranes (MAMs) provide a platform for proteins and channels involved in Ca 2+ transfer between the endoplasmic reticulum (ER) and mitochondria. Deregulated Ca 2+ signaling and proteins regulating ER-mitochondria interactions have been linked to liver diseases and intensively investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In addition, oncogenes and tumor suppressor proteins can play other roles in cancer development through Ca 2+ signal regulation, such as resistance to apoptosis. Because mitochondrial Ca 2+ overload is related to apoptosis and death, modifying ER−mitochondria Ca 2+ transfer at the MAM will change the sensitivity of apoptosis, and tumor cells can acquire resistance to cell death accordingly [ 136 ]. For example, by inhibiting IP 3 R-mediated Ca 2+ signaling or increasing the transmembrane distance at the MAM, the efficiency of ER−mitochondria Ca 2+ transfer can be reduced, so as to decrease the sensitivity of tumor cells to apoptosis [ 137 ] ( Figure 4 ).…”
Section: Mitochondrial Ca 2+ and Tumor Cell Apoptosismentioning
confidence: 99%
“…In addition, oncogenes and tumor suppressor proteins can play other roles in cancer development through Ca 2+ signal regulation, such as resistance to apoptosis. Because mitochondrial Ca 2+ overload is related to apoptosis and death, modifying ER−mitochondria Ca 2+ transfer at the MAM will change the sensitivity of apoptosis, and tumor cells can acquire resistance to cell death accordingly [ 136 ]. For example, by inhibiting IP 3 R-mediated Ca 2+ signaling or increasing the transmembrane distance at the MAM, the efficiency of ER−mitochondria Ca 2+ transfer can be reduced, so as to decrease the sensitivity of tumor cells to apoptosis [ 137 ] ( Figure 4 ).…”
Section: Mitochondrial Ca 2+ and Tumor Cell Apoptosismentioning
confidence: 99%
“…The Ca 2+ released from ER can be efficiently transferred to mitochondria, resulting in mitochondrial Ca 2+ overload, a key factor in the opening of mitochondrial permeability transition pores to increase mitochondrial ROS production and reduce ATP production. 46,47 High Ca 2+ levels and the subsequent loss of the MMP initiated the intrinsic apoptosis pathway. Tsai et al 48 have shown that graphene can lead to the release of Ca 2+ from ER and then activate the mitochondria-dependent apoptosis signaling pathway.…”
Section: And S3-s19 †)mentioning
confidence: 99%
“…Recent studies have shown that the regulation of ERMCs and mitochondrial dynamics are two closely intertwined processes ( Friedman et al, 2011 ). Studies have shown that the sites of MAMs in rat heart cells coincide with the outer mitochondrial membrane (OMM) – inner mitochondrial membrane (IMM) contact sites, and therefore, MAMs may form calcium channel complexes to regulate Ca 2+ transport between the endoplasmic reticulum and mitochondria ( Jin et al, 2021 ). The inositol 1,4,5-triphosphate receptor (IP3R) is located in the ER membrane and regulates Ca 2+ release, and voltage-dependent anion selective channel protein (VDAC) 1 is a Ca 2+ uptake channel on the OMM ( Szabadkai et al, 2006 ).…”
Section: Structure Of Endoplasmic Reticulum-mitochondria Contactsmentioning
confidence: 99%